(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The use of authentic materials—texts, audio, and visual content created for real-life communication—has become increasingly significant in ESL (English as a Second Language) education. These materials offer learners exposure to natural language use, diverse accents, and real-world contexts, which are often absent in traditional textbook-based learning. This article explores the benefits and challenges of integrating authentic materials in the ESL classroom and provides strategies for effective implementation. Authentic resources not only enhance linguistic competence but also boost learners’ cultural awareness, motivation, and communicative confidence.